2006
DOI: 10.1161/01.hyp.0000217128.41284.78
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Continuous Positive Airway Pressure Versus Supplemental Oxygen on 24-Hour Ambulatory Blood Pressure

Abstract: Abstract-Obstructive sleep apnea (OSA) is associated with recurrent episodes of nocturnal hypoxia and increased risk for development of systemic hypertension. Prior studies have been limited, however, in their ability to show reduction in blood pressure after continuous positive airway pressure (CPAP) therapy, and the effect of supplemental oxygen alone on blood pressure in OSA has not been evaluated. We performed a randomized, double-blind, placebo-controlled study comparing the effects of 2 weeks of CPAP ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(103 citation statements)
references
References 74 publications
3
96
2
2
Order By: Relevance
“…It has been suggested that hypoxia and frequent periodic arousals from sleep may underlie the increased sympathetic nervous activity in the presence of OSAS, although arousals seem to be more significant [10,30]. Consistent with a reduction of sympathetic nerve activity, the present authors found that 4 weeks of CPAP therapy decreased 24-h urine normetanephrine excretion by 26%.…”
Section: Sympathetic Activitysupporting
confidence: 82%
“…It has been suggested that hypoxia and frequent periodic arousals from sleep may underlie the increased sympathetic nervous activity in the presence of OSAS, although arousals seem to be more significant [10,30]. Consistent with a reduction of sympathetic nerve activity, the present authors found that 4 weeks of CPAP therapy decreased 24-h urine normetanephrine excretion by 26%.…”
Section: Sympathetic Activitysupporting
confidence: 82%
“…Our study was primarily focused on changes in BC. We thus did not record changes in other clinically important measures such as blood pressure, which has been shown to decrease in several trials (69)(70)(71). Finally, using a prepost design, we were able to detect changes within specific age categories only.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, sham CPAP is not inert and may raise BP. 40 Moreover, the BP analyses were obtained in a blind fashion.…”
Section: Drager Et Al Osa Prehypertension and Masked Hypertensionmentioning
confidence: 99%